Assessment of the conservation status of natural and semi-natural patches associated with urban areas through habitat suitability indices - Natale, Evangelina Sandra (2015)
Urban environments rely on the surrounding natural ecosystems remnants as providers of ecosystem functions, therefore these areas not only support a unique biodiversity but also have a social value for maintaining public health and wellbeing. For this reason, urbanization is considered to be one the biggest threats to ecosystems, leading to native biodiversity simplification and, thus, to a detriment of the provided ecosystem services. Moreover, this change in land use results in high levels of landscape fragmentation and modification in areas surrounding the habitat remnants which, in consequence, become inadequate for many native species. In this context, it is important that urban planners have the information to assess the possible consequences of future changes in land use in order to increase the landscape chances of supporting both, native biodiversity and the needs of a growing human population. The objective of the present work is to evaluate the ecological integrity of natural and semi-natural vegetation patches immersed in an urban area in order to generate a conceptual framework for landscape assessment that allows urban planners to envision the best choice for city development at a given place. To do so, we developed a quantitative integral environmental evaluation index that includes ecological characterization, geological characterization, and environmental characterization (presence of anthropic disturbance) of the assessed area. We conclude that the index we have generated in this work is suitable to be used as a management tool to allow an unbiased valuation and to identify managing situations that require a short term response.